Women's Use of Intimate Partner Aggression: Associations With Sexist Experiences - Miles-McLean, Haley A. (Violence against women, 2025)
Identity-based discrimination experiences have been associated with intimate partner aggression (IPA) use, yet very little research has examined sexist discrimination. This study explored whether women's experiences of sexist discrimination are associated with their IPA use. Participants were 626 predominantly white, cisgender, heterosexual women who completed self-report measures online. Women's sexist experiences were significantly and positively correlated with their IPA use, even after controlling for recent stressful experiences and gender-based violence exposures. Psychological distress symptoms significantly mediated the relation between sexist experiences and IPA use. The findings demonstrate the importance of considering the role of sexism in women's IPA.